Design of Frequency- and Pattern-Reconfigurable Wideband Slot Antenna - Liping Han; Caixia Wang; Wenmei Zhang; Runbo Ma; Qingsheng Zeng (International Journal of Antennas and Propagation)
A wideband slot antenna with frequency- and pattern-reconfigurable characteristics for TD-LTE (3.4–3.8 GHz) and C-band (3.7–4.2 GHz) applications is proposed. The antenna consists of two symmetric slots that are fed by a fork-shaped microstrip line. Two PIN diodes are loaded in the slots to produce two different frequency bands. Meanwhile, two additional PIN diodes are inserted in the feed line to achieve the pattern reconfigurability. The wideband operation is realized by using the symmetric slots and fork-shaped feed line. Simulated and measured results show that the antenna provides 25° and 20° beam-steering in 3.4–3.8 and 3.7–4.2 GHz bands, respectively. Also, an impedance bandwidth of at least 12.8% is obtained in the operating bands.